Inclusion of Halal Product Provisions Consumption in order to meet business competition ethics - Dharma Setiawan Negara; Samuel Dharma Putra Nainggolan; Lufsiana Lufsiana (Jurnal Indonesia Sosial Teknologi, 2024)
In 2024, the number of Muslim population in the world in general and specifically in Indonesia will increase. Of course, this is also followed by market demand for consumer products that are guaranteed halal. In the past, halal product certification was carried out by the Indonesian Ulema Council based on applicable laws and regulations. Currently, there are improvements both in terms of regulation and from the side of institutions authorized to issue halal certification for a consumer product, one of which is the establishment of the Halal Product Assurance Organizing Agency (BPJPH) which is authorized to issue halal certification of consumer products. This research is a normative legal research that uses a statutory approach, and a conceptual approach to answer legal issues and produce findings regarding institutions authorized to issue halal certification of applicable consumer products.